مفهوم إدارة المبادرات الأهداف والمحفزات والمعوقات: دراسة وصفية تحليلية - Abubaker Ahmed,; Mohammad Nashief S. Pisomi (Universiti Sains Islam Malaysia, 2024)
Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.